10.1016/s1558-0164(08)70402-4 (CrossRef Listing of Deleted DOIs, 2000)
Left bundle branch area pacing (LBBAP) has emerged as a promising alternative to right ventricular apical pacing in patients with congenital heart disease (CHD), yet its application in this population remains underexplored despite unique anatomical and physiological challenges. This review synthesizes current evidence on LBBAP in CHD, including anatomical considerations of the conduction system, lead selection between lumenless and stylet-driven leads, technical modifications for different substrates, and clinical outcomes. In congenitally corrected transposition of the great arteries (CCTGA), the paradoxically anterior conduction system creates favorable anatomy for LBBAP, with reported success rates of 86%-100% in small observational series. CHD-specific data from Moore et al. demonstrated superior QRS narrowing with conduction system pacing (CSP) compared to conventional CRT (35 vs. 14 ms; p = 0.04). One randomized trial and multiple meta-analyses comparing lumenless and stylet-driven leads demonstrate comparable success rates but distinct safety profiles, with implications for lead choice in CHD patients requiring lifelong pacing. The 2023 HRS/APHRS/LAHRS and 2025 ACC/AHA guidelines now recognize CSP as a therapeutic option in selected patients, though these endorsements are not specific to LBBAP in CHD. CHD-specific evidence remains limited to case series and small observational studies. This review provides a practical framework for patient selection, lead choice, and procedural planning while identifying key research priorities for this growing patient population.